The effect of counterfactual treatment on the consistency between ethnic minority values and value-expressive behavioral intentions - Yang, Yanli (Frontiers in Psychology, 2025)
BackgroundConsistency in values and behaviors has always been controversial in academia, particularly under specific situations. However, little is known about how situations affect the consistency of minority ethnic values with their value-expressive behaviors (reflecting the strength of an internal value characterized by the importance of ethnicity). Counterfactual thinking has been established to have a significant impact on behavioral change and performance improvement. Therefore, based on the theory of value–behavior consistency and the operational definition of minority ethnic values and counterfactual treatment, the study aimed to examine how counterfactual thinking affects the consistency between minority ethnic values and value-expressive behaviors.MethodsUsing convenience sampling, 251 Chinese ethnic minority college students completed the Chinese Minority Ethnic Values Questionnaire (CMEVQ) to evaluate levels of minority ethnic values; 27% with the highest and lowest levels (total: 135) were divided into “ethnic closeness” and “ethnic alienation” groups. Subsequently, we selected five typical ethnic behavioral descriptions from the Chinese Minority Ethnic Value-Expressive Behavior Questionnaire (CMEVEBQ) and altered them to factual, counterfactual, and empirical thinking materials. Finally, both groups, as counterfactual priming groups, completed a pre-test (factual thinking baseline) and post-test (counterfactual thinking priming) using a sequential priming paradigm, which involved making choices regarding behavioral intention ratings and priming judgment; they, as empirical priming groups, did the similar quasi-experimental procedures 3 months later with an empirical thinking tasks included in the post-test.ResultsThe results indicated that (1) counterfactual treatment affect ethnic minorities in making choices regarding ethnic value-expressive behavioral intentions (promoting and inhibiting them); (2) in counterfactual treatment, ethnic minorities express their ethnic behavioral intentions in ethnic value-consistent directions; and (3) in counterfactual treatment, minorities with different levels of ethnic-minority-value have different levels of consistency in terms of ethnic values and value-expressive behavioral intentions.DiscussionOur findings indicate that ethnicity can protect and motivate ethnic minorities to maintain consistency between minority ethnic values and value-expressive behavioral intentions, which have important theoretical and practical implications for the value theory. This provides empirical evidence for enhancing national cohesion in forging a strong sense of community for the Chinese nation.